2016
DOI: 10.1186/s12968-016-0258-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and clinical significance of right ventricular mechanics in pulmonary hypertension evaluated with cardiovascular magnetic resonance feature tracking

Abstract: BackgroundPrognosis in pulmonary hypertension (PH) is related to right ventricular (RV) function. Quantification of RV mechanics may offer additive value. The objective of our study is to determine the feasibility and clinical and prognostic value of RV strain analysis by cardiovascular magnetic resonance (CMR) based feature tracking (FT) in PH.MethodsWe retrospectively enrolled 116 patients (age 52.2 ± 12 years, 73.6 % women) referred to CMR for PH evaluation who underwent right heart catheterization within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 37 publications
7
97
1
4
Order By: Relevance
“…Recent studies have shown that the symptoms and outcomes of PAH are largely related to RV function (5) . Echocardiography is currently the image modality most widely used in evaluating the structure and function of the RV (6) . However, echocardiography is operator dependent and the image quality is often inadequate, especially for the RV (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the symptoms and outcomes of PAH are largely related to RV function (5) . Echocardiography is currently the image modality most widely used in evaluating the structure and function of the RV (6) . However, echocardiography is operator dependent and the image quality is often inadequate, especially for the RV (7) .…”
Section: Introductionmentioning
confidence: 99%
“…It is no doubt that RVGLS is the most frequently mentioned index and the only RV strain parameter investigated in prior echocardiography studies, partly because it is tedious to acquire multiple RV‐focused short‐axis views to measure RVGCS and RVGRS . In pulmonary hypertension, de Siqueira et al demonstrated the prognostication of RV circumferential deformation, which was also the most significant RV deformation parameter for our secondary endpoint. Because RVGRS was not obtained in their study, comparison between RVGRS and RVGCS is unknown.…”
Section: Discussionmentioning
confidence: 92%
“…In an RV CMR‐FT analysis, Park et al reported good correlations of RVGLS between 2D speckle tracking echocardiography and MR‐FT in a small group of patients with ischemic cardiomyopathy. de Siqueira et al demonstrated the utility of RV global circumferential strain rate in prognostication in pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial deformation (strain), measured using cardiac magnetic resonance feature tracking, has shown to contain additive value in predicting outcome, when compared to conventional measurements of ventricular function and volume in various cardiovascular diseases [9,10]. Even in the absence of impaired ejection fraction (EF), strain variables are affected in heart failure, indicating that strain could be a more sensitive marker of myocardial dysfunction than EF [11].…”
Section: Introductionmentioning
confidence: 99%